Adjusting key performance indicators in ART laboratories according to controlled ovarian stimulation protocol - Chen, Wei; Cheng, Shiyuan; Liu, Yan; Wu, Zhaoting; Zhang, Fuli; Huang, Xianju; Yao, Guidong; Song, Wenyan; Jin, Haixia (Frontiers in Physiology, 2025)
BackgroundReliable key performance indicators (KPIs) have been proposed to facilitate the quality management of embryo laboratories. However, the effects of controlled ovarian stimulation (COS) protocols on KPIs have not been adequately explored. This study aims to assess the variation in KPIs across four different COS protocols.MethodsWe retrospectively analyzed 51,728 IVF/ICSI cycles in our center between 2014 and 2022. They were divided into four groups based on COS protocols: follicular phase long-acting (FPL) GnRH-a long, luteal phase short-acting (LPS) GnRH-a long, GnRH-ant, and micro-stimulation protocol groups. Several KPIs were compared across the four groups, and the results were validated in three age bands (<35 years, 35–38 years, and >38 years). Multivariable regression analysis was conducted to assess the effect of COS protocols on KPIs.Results1) Significant differences were observed among the four groups in total blastocyst development rate (BLR) (56.2%, 54.1%, 49.7%, 29.5%, p < 0.001), total good blastocyst development rate (GBLR) (26.8%, 30.4%, 21.1%, 13.1%, p < 0.001), and implantation rate (46.6%, 30.7%, 24.2%, 13.1%, p < 0.001). 2) The LPS GnRH-a group showed a higher total GBLR (30.4%, 26.8%, p < 0.001) but a lower implantation rate compared to the FPL GnRH-a group (30.7%, 46.6%, p < 0.001). 3) Significant differences in KPIs were observed across all age groups, with the largest differences seen in women under 35 years 4) Multivariate logistic regression analysis revealed that these KPIs were significantly associated with the COS protocol.ConclusionCOS protocols significantly impact KPIs, suggesting that explore reliable KPIs according to treatment protocols could better evaluate the laboratory efficacy and provide a theoretical basis for personalized strategies for patients.